2014
DOI: 10.1038/bmt.2014.61
|View full text |Cite
|
Sign up to set email alerts
|

Value of liver elastography and abdominal ultrasound for detection of complications of allogeneic hemopoietic SCT

Abstract: Hepatic complications contribute to morbidity and mortality after allogeneic hemopoietic SCT. Liver Doppler ultrasound and elastography represent promising methods for pretransplant risk assessment and early detection of complications. Ultrasound (liver and spleen size, liver perfusion) and elastography (transient elastography (TE); right liver lobe acoustic radiation force impulse imaging (r-ARFI); left liver lobe ARFI (l-ARFI)) were prospectively evaluated in patients with indications for allo-SCT. Measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…We have shown that the median LSM values of patients with VOD/SOS were significantly higher than those of patients with other therapy-associated liver complications (eg, acute cholecystitis, cholangitis, DILI related to antimycotic drugs, hepatic GVHD, isolated liver biochemical alterations, fulminant Epstein-Barr virusrelated hepatitis reactivation) regardless of CTC grade (Figure 4). This result is apparently in contrast with the findings of Karlas et al [29], who reported significantly higher LSM values measured by TE in 5 of 59 HSCT recipients who developed severe hepatic involvement after HSCT (CTC grade 4 to 5) compared with the others who did not (mean, 6.2 § 1.5 kPa versus 4.7 § 1.7 kPa). A possible explanation for this discrepancy is the fact that VOD/SOS was not analyzed separately but was included in the severe complication group without any specifications.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We have shown that the median LSM values of patients with VOD/SOS were significantly higher than those of patients with other therapy-associated liver complications (eg, acute cholecystitis, cholangitis, DILI related to antimycotic drugs, hepatic GVHD, isolated liver biochemical alterations, fulminant Epstein-Barr virusrelated hepatitis reactivation) regardless of CTC grade (Figure 4). This result is apparently in contrast with the findings of Karlas et al [29], who reported significantly higher LSM values measured by TE in 5 of 59 HSCT recipients who developed severe hepatic involvement after HSCT (CTC grade 4 to 5) compared with the others who did not (mean, 6.2 § 1.5 kPa versus 4.7 § 1.7 kPa). A possible explanation for this discrepancy is the fact that VOD/SOS was not analyzed separately but was included in the severe complication group without any specifications.…”
Section: Discussioncontrasting
confidence: 99%
“…To date, among these techniques, only transient elastography (TE) [28À30] and point-shear wave elastography by acoustic radiation force impulse imaging [29,31] have been evaluated for assessment of liver complications in pediatric patients undergoing HSCT. No study has yet been reported on the role of LSM in VOD/SOS assessment in the setting of adult HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper has shown that LS measurement using ARFI (Acoustic Radiation Force Impulse) and Fibroscan could represent an additional diagnostic parameter for adult patients with suspected post-transplant hepatic injury; in fact, LS pretransplant values using ARFIo 1.25 m/s were correlated with the absence of severe complications after allo-HSCT. 14 The aim of our study was to verify the role of LS measurement in predicting VOD development in a pediatric population who underwent HSCT using Fibroscan.…”
mentioning
confidence: 99%
“…The possible role for on the use of LSM in the HSCT setting was suggested by Karlas et al, who stated that LSM, assessed both by TE (FibroScan®, Echosens, France) and ARFI, pSWE, could predict the onset of hepatobiliary complications in adult patients undergoing HSCT. In addition, Colecchia et al first and Reddivalla et al subsequently have demonstrated that LSM, using TE and two‐dimensional SWE, respectively, had a sudden increase up to more than a week before the diagnosis of VOD/SOS in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%
“…reflects the health of the liver that increases due to several pathogenetic factors (fibrosis, inflammation, congestion, central venous pressure, and cholestasis) and which is used as the standard non-invasive diagnostic assessment of portal hypertension in patients with chronic liver disease. 9 The possible role for on the use of LSM in the HSCT setting was suggested by Karlas et al, 10 who stated that LSM, assessed both by TE (FibroScan®, Echosens, France) and ARFI, pSWE, could predict the onset of hepatobiliary complications in adult patients undergoing HSCT. In addition, Colecchia et al 11 first and Reddivalla et al 12 subsequently have demonstrated that LSM, using TE and two-dimensional SWE, respectively, had a sudden increase up to more than a week before the diagnosis of VOD/SOS in pediatric patients.…”
mentioning
confidence: 99%